The Growing Toolbox for Protein Synthesis Studies. Issue 8 (August 2017) - Iwasaki, Shintaro; Ingolia, Nicholas T.
Abstract : Protein synthesis stands at the last stage of the central dogma of molecular biology, providing a final regulatory layer for gene expression. Reacting to environmental cues and internal signals, the translation machinery can quickly tune the translatome from a pre-existing pool of RNAs, before the transcriptome changes. Although the translation reaction itself has been known since the 1950s, the quantitative or even qualitative measurement of its efficacy in cells has posed experimental and analytic hurdles. In this review, we outline the array of state-of-the-art methods that have emerged to tackle the hidden aspects of translational control. Trends: Fluorescent labeling of newly synthesized protein measures overall translation activity by conventional microscopic analysis and fluorescence-activated cell sorting (FACS). Mass spectrometry analysis with specific isolation of newly synthesized protein monitors the differential changes in the proteome caused by translation alteration. Ribosome profiling and its derivative methods globally survey in vivo kinetics of translation, local translatome, and co-translational events. In vivo single-molecule analysis addresses the kinetic and dynamic fluctuation of translation, molecule by molecule, in real time.